Caregivers' experiences in the management of children with epilepsy: A Systematic synthesis of qualitative studies. (March 2023) - Yang, Liling; Ji, Jianlin; Lu, Qunfeng; Tang, Ping; Jiang, Yan; Yang, Hanlin; Tang, Wenjuan
Highlights: Many studies have shown that caregivers of children with epilepsy face greater psychological burden and poorer quality of life. However, few studies have fleshed out the caregiving experiences. This study describes the unique experiences that epilepsy presents to caregivers, not only in terms of the difficulties of the caregiving process, but also in terms of the twists and turns of the diagnosis process, concerns about the child's future, and changes in self-life status. The study describes the multidimensional social support that caregivers need and analyzes the reasons. Understanding the difficulties caregivers face in the caregiving process and the need for support helps to build interventions that provide better support to caregivers. While many quantitative studies indicate poor quality of life in caregivers' of children and adolescents with epilepsy, this study used a meta-aggregation to understand the real experiences of caregivers of children and adolescents with epilepsy. Abstract: Objective: Childhood is the prime age for epilepsy onset. Adults in the family of affected children often become caregivers. Providing care for children with epilepsy may affect the caregivers' quality of life. There is a paucity of literature reviewing the experiences of caregivers of children with epilepsy. Therefore, we summarised the best available evidence exploring caregivers' experiences in caring for children with epilepsy. Method: Published papers in PubMed, CINAHL, Embase, Cochrane Library, Web of Science, Scopus, and PsycINFO databases were identified by two researchers. All search results were imported into EndNote X20. Two reviewers independently extracted the data using Microsoft Excel. The Critical Appraisal Skill Program systematic review checklist was used to evaluate the quality of the included articles. Data of the included studies were extracted by two independent reviewers using a standardised form. These findings were synthesised using a meta-aggregative approach. Results: A total of 12 studies were included in this meta-synthesis. In total, 260 findings were identified. These findings were aggregated into 13 categories, which were synthesised into four main themes: (i) burden experienced by caregivers, (ii) challenges experienced by caregivers, (iii) lack of social support, and (iv) adaptation to disease conditions. Significance: The synthesised studies present multiple perspectives on the burdens and challenges encountered by caregivers of children with epilepsy. Caregivers require support from a variety of sources, not only from their families but also society at large. Providing care to children with epilepsy is a dynamic experience for caregivers.